2016
DOI: 10.1007/s11103-016-0529-9
|View full text |Cite
|
Sign up to set email alerts
|

UV-mediated Chlamydomonas mutants with enhanced nuclear transgene expression by disruption of DNA methylation-dependent and independent silencing systems

Abstract: In this investigation, we succeeded to generate Chlamydomonas mutants that bear dramatically enhanced ability for transgene expression. To yield these mutants, we utilized DNA methyltransferase deficient strain. These mutants must be useful as a plant cell factory. Chlamydomonas reinhardtii (hereafter Chlamydomonas) is a green freshwater microalga. It is a promising cell factory for the production of recombinant proteins because it rapidly grows in simple salt-based media. However, expression of transgenes int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…Such an enhancer could function to recruit the elements of the transcription machinery by either direct transcription factor binding or acting on the epigenetic level, making the insertion site more accessible to regulatory protein binding. It was previously reported that knock out of the met1 gene leads to a globally reduced DNA methylation status, and consequently to higher transgene expression from the nuclear genome of C. reinhardtii ( 13 , 49 ). The strain UVM11, which also exhibits improved nuclear transgene expression capacities, reportedly has an reduced Histone 3 occupancy, increased Histone 4 acetylation and an reduced H3 Lysine 9 monomethylation status at the gene of interest site ( 15 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an enhancer could function to recruit the elements of the transcription machinery by either direct transcription factor binding or acting on the epigenetic level, making the insertion site more accessible to regulatory protein binding. It was previously reported that knock out of the met1 gene leads to a globally reduced DNA methylation status, and consequently to higher transgene expression from the nuclear genome of C. reinhardtii ( 13 , 49 ). The strain UVM11, which also exhibits improved nuclear transgene expression capacities, reportedly has an reduced Histone 3 occupancy, increased Histone 4 acetylation and an reduced H3 Lysine 9 monomethylation status at the gene of interest site ( 15 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although genetic manipulation is well established in C. reinhardtii , the capacity for robust and reliable transgene expression from the nuclear genome, and consequently successful genetic engineering, is limited by its characteristic low transgene expression levels ( 8–11 ). Several attempts have been made to overcome this limitation by: cell line improvement ( 12 , 13 ), design of synthetic promoters ( 14 ), and transgene codon optimization ( 15 , 16 ). However, most reports of robust genetic engineering in C. reinhardtii involve the expression of only reporter proteins with relatively short coding sequences (CDS) ( 15 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…When the met1 strain was further mutated by UV irradiation, we obtained met1(UVM)-47A and B mutants, which enable robust expression of nuclear transgenes regardless of the genomic position of the insertion, due to disruption of DNA methylation-dependent and -independent silencing systems. Moreover, met1(UVM) mutants were more capable of robustly expressing native, F o r P e e r R e v i e w fluorescent, or heterologous proteins than were other Chlamydomonas strains tested (Kurniasih et al 2016).…”
Section: Background Strainsmentioning
confidence: 98%
“…These strains have been used as background strains for protein subcellular localization studies, as host strains for protein secretion, and for the production of terpene squalene (Kajikawa et al 2015, Lauersen et al 2013. However, these UVM strains are still subjected to transgene silencing, probably because the gene silencing mechanisms have not been completely knocked out (Kong et al 2015, Kurniasih et al 2016).…”
Section: Background Strainsmentioning
confidence: 99%
“…In the case of nuclear expression, genetic engineering faces two challenges: the improvement of yields and the genetic stability of the transformed clones (Rosales-Mendoza, 2016b). In an effort to overcome these obstacles, UV mutagenesis has been used to generate Chlamydomonas reinhardtii strains with improved transgene expression (showing yields up to 0.2% TSP; Neupert et al, 2009; Kurniasih et al, 2016). Secretion approaches have also been implemented in these mutant strains, leading to yields up to 10 mg of secreted reporter protein per liter of culture (Lauersen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%